PENGARUH PENGGUNAAN ALAT PERAGA MEAN BOARD TERHADAP PEMAHAMAN KONSEP SISWA KELAS VIII PADA MATERI STATISTIKA - Rica Angrayani; Widiawati; Reza Lestari (STKIP Subang, 2026)
The purpose of this study was to determine the effect of using the Mean Board teaching aid on students’ conceptual understanding in statistics material for eighth grade students at SMP Muhammadiyah Pagar Alam in the academic year 2025/2026. The method used in this study was an experimental method with a Pretest-Posttest Control Group Design. The study involved 59 students consisting of 30 students in the experimental class and 27 students in the control class. The experimental class was taught using the Mean Board teaching aid, while the control class was taught using a conventional approach. The data collection techniques included normality testing, homogeneity testing, and the independent sample t-test. The results of the study showed that the average conceptual understanding of students taught using the Mean Board teaching aid was better than that of students taught using the conventional approach. This indicates that the use of the Mean Board teaching aid has an effect on students’ conceptual understanding in statistics material. Therefore, the Mean Board teaching aid is very helpful in assisting students to understand learning materials.